Antibiotic ecotoxicity and resistance risks in resource-constrained chicken and pig farming environments - Gudda, Fredrick; Muloi, Dishon; Nganga, Fredrick; Nolari, Cynthia; Gao, Y.; Moodley, Arshnee (Nature Research, 2024)
Antimicrobial resistance (AMR) data from agroecosystems in low- and middle-income countries is limited. We surveyed chicken (n = 52) and pig (n = 47) farms in Kenya to understand AMR in animal-environment pathways. Using LC-MS/MS, we validated the methods for analyzing eight common antibiotics and quantified the associated risks. Chicken compost (25.8%, n = 97/376) had the highest antibiotics prevalence, followed by pig manure-fertilized soils (23.1%, n = 83/360). The average antibiotic concentration was 63.4 µg/kg, which is below the environmentally relevant threshold (100 µg/kg), except for trimethoprim (221.4 µg/kg) among antibiotics and pig manure-fertilized soils (129.3 µg/kg) across sample types. Similarly, the average AMR risk quotient (RQ) was low (RQ < 0.1), except for trimethoprim and sulfamethoxazole (RQ ≥ 1). Ecotoxicity and AMR risks increased with flock size and the number of antibiotics used by pigs. Continuous environmental monitoring and large-scale studies on antibiotic contamination are crucial for evidence-based pollution control and the effective mitigation of environmental AMR.